Influence of Inlet Air Temperature and its Effects on Combustion using Liquid Fuel Combustion in Taper Can Gas Turbine Combustor - D. R. Srinivasan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The extent of vaporization droplets of liquid fuel that are sprayed into air stream of turbulent swirling flow in a can gas turbine combustor appears to have a very high influence on combustion and emissions thereby performance of the combustor. The investigations containing both experimental as well as numerical in nature was carried out earlier researchers to enhance the fuel vaporization. In this paper a new method is proposed to predict the effects of inlet air temperature on combustion characteristics simulated using a taper can type combustion chamber. A sector of this can type combustor was modelled having an included angle of 51.42o and simulated for combustion process using CFD code star-CD with inlet air temperature entering the combustor after compression varied from 500 K to 1000 K. The turbulence model used in this simulation was model along with high Reynolds number by selecting standard wall treatment. Non-premixed type of combustion method was used for simulation of combustion in the combustion chamber by selecting eddy break-up model called Magnussen’s (EBU). The tracking of atomised fuel droplets was done by selecting Lagrangian multiphase model as it contains two phases i.e. liquid fuel droplets injected into turbulent swirling air stream inside the combustion chamber. Reitz Diwakar model was used as droplet breakup model selected and Bai’s model was used for droplets of fuel colliding with the wall. Rosin-Rammler method for classifying droplet diameters and probability density functions. All peripheral boundaries of combustion chamber was taken as adiabatic in nature. All sector walls separated by 51.42o were imposed with Symmetry boundary conditions. A well-defined three step reaction model was adopted as combustion reaction that involves liquid fuel as energy source and oxidiser as oxygen with end products of combustion as water vapour and carbon dioxide. As part of grid independency check the model was meshed. Every meshed model has as specified cell size that commences from 3mm to 8mm having step size of 1 mm. The results obtained from meshed models of 3mm and 4mm cell sizes were replicating each other. For less computational time 4mm cell size was used to carry out the investigations. Different cases were run for many inlet air temperatures starting from 500 K to 1000 K with an increase of 100 K in each step size. The results thus obtained were displayed as centre section contour plots of temperature, turbulent kinetic energy drawn along the axial direction till the exit of combustor. The values obtained at the outlet of combustor are the average values and graphical in nature. From this analysis, the inlet air temperature had played pivotal role resulting in enhanced liquid fuel droplets evaporation and combustion in the combustion chambe